2011
DOI: 10.4028/www.scientific.net/amr.236-238.1902
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Silk Fibroin Microspheres

Abstract: TheBombyx morisilk fibroin microspheres with controllable size were prepared by electrostatic spraying and freeze-drying method. The effects of solution concentration, voltage and flow rate on the sphere size were discussed. The morphology of microspheres was observed by scanning electron microscopy (SEM). The influence of ethanol treatment on the molecular conformation of silk fibroin microspheres was investigated by XRD and FT-IR spectra. The results indicated that the silk fibroin microspheres with diameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…It is worth mentioning that among the three major conformations, the β-sheet is regarded as the most crystalline structure. In fact, it is the changing conformation, which renders alcohol treated fibroin water insoluble [19].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth mentioning that among the three major conformations, the β-sheet is regarded as the most crystalline structure. In fact, it is the changing conformation, which renders alcohol treated fibroin water insoluble [19].…”
Section: Resultsmentioning
confidence: 99%
“…Thus far, a variety of techniques have been used to use SF in different forms such as hydrogels [11], tubes [16], sponges [17], composites [18], thin films [13], microspheres [19], fibers [20], and fabrics [21] for life science applications e.g. drug delivery [22], wound healing [23], [24], tissue engineering [12], [13] and regenerative medicine [21].…”
Section: Introductionmentioning
confidence: 99%
“…In 2014, Qu et al [75] demonstrated the preparation of silk fibroin nanoparticles (SFN) by electrospraying to produce controlled-release carriers of cisplatin (CDDP)-a chemotherapeutic agent-in order to reduce its cytotoxicity and adverse effects on healthy tissue. Silk fibroin (SF) was extracted from raw silk fibres as previously described by Wang et al [76], obtaining an aqueous protein solution. Then, glycerin was added to the SF solution (30% vs. protein).…”
Section: Electrosprayingmentioning
confidence: 99%
“…Pure silk fibroin has been used to develop MCs for cell culture under mild processing conditions. In the work of Wang et al [63], fabrication of these materials was achieved using a high voltage electrostatic field, in order to obtain fibroin spherical droplets. The silk spheres were posteriorly subject to freeze‐drying, resulting in highly porous biomaterials with diameters ranging from 208.4 to 727.3 μm.…”
Section: Silk Fibroin‐based Mcsmentioning
confidence: 99%
“…Although the use of bioreactors to perform cell seeding on MCs is a promising way to mimic and simulate the biological environment in order to obtain 3D constructs, studies of fibroin‐based MCs with dynamic cell culture are still scarce [60–74].…”
Section: Future Perspectivesmentioning
confidence: 99%